Ethnic minorities and prescription medication; concordance between self-reports and medical records - Spreeuwenberg Peter; Foets Marleen; Devillé Walter; van Dijk Liset; Uiters Ellen; Groenewegen Peter P (BMC, 2006)
Abstract Background Ethnic differences in health care utilisation are frequently reported in research. Little is known about the concordance between different methods of data collection among ethnic minorities. The aim of this study was to examine to which extent ethnic differences between self-reported data and data based on electronic medical records (EMR) from general practitioners (GPs) might be a validity issue or reflect a lower compliance among minority groups. Methods A cross-sectional, national representative general practice study, using EMR data from 195 GPs. The study population consisted of Dutch, Turks, Surinamese, Antilleans and Morrocans. Self-reported data were collected through face-to-face interviews and could be linked to the EMR of GPs. The main outcome measures were the level of agreement between annual prescribing rate based on the EMRs of GPs and the self-reported receipt and use of prescriptions during the preceding 14 days. Results The pattern of ethnic differences in receipt and use of prescription medication depended on whether self-reported data or EMR data were used. Ethnic differences based on self-reports were not consistently reflected in EMR data. The percentage of agreement above chance between EMR data and self-reported receipt was in general relative low. Conclusion Ethnic differences between self-reported data and EMR data might not be fully perceived as a cross-cultural validity issue. At least for Moroccans and Turks, compliance with the prescribed medication by the GP is suggested not to be optimal.